Nature and social attitude in folklore entitled Timun Mas: Eco-critical study - Nanik Setyowati; Emzir Emzir; Ninuk Lustyantie (English, 2020)
This research traces the relationship between a character's existence, ecological insight, and cultural values ​​in folklore. Whether it is recognized or not, in Indonesia, folklore has the power to explore nature. To achieve that goal, this research approach is qualitative that is supported by a content analysis method. The source of research data is Timun Mas Folklore. The study of literary perspective (environment) in eco-criticism can construct the wisdom of the environment itself and the study of environmental literature perspective, can be focused on ethical studies (1) respect for nature, (2) responsibility for nature, (3) solidarity towards nature, (4) affection and care for nature, and (5) attitudes not to disturb the natural life displayed in literary works. Through this study, there are several findings obtained that are water environment pollution, habitat destruction, and management of nature or the environment.